Predicting relationship quality with itself? A single general factor captures most of the variance across 34 common relationship measures - James J. Kim; Samantha Joel; Ariana M. Gonzales; Brett A. Murphy; Jacqueline C. Perez; Victor A. Kaufman; Thomas N. Bradbury; Paul W. Eastwick; Benjamin R. Karney (PLoS ONE, 2026)
In relationship science, researchers have generated a wide array of constructs and corresponding self-report measures to characterize, explain, and predict relationship quality – the foremost studied outcome in the field. Collectively, however, the boundaries among these variables remain unclear. In the current research, we examined the extent to which measures of relationship quality and other important relationship constructs are empirically separable from one another. Across two studies of US census-matched participants (total N = 3,439), we applied latent variable techniques (e.g., exploratory bifactor analysis) on broad pools of items representing various prominent relationship-specific constructs. Results revealed robust evidence that a single general factor Q (representing global relationship sentiment) accounts for a vast majority of common variance across distinct relationship measures. Thus, respondents appear to draw primarily on their overall global relationship evaluations when reporting on an array of presumably-distinct relationship facets. This is consistent with a ‘sentiment override’ perspective. Our findings provide novel empirical evidence for a relationship-specific response bias that challenges prevailing assumptions and practice in the field, including the widespread use of self-report methods to capture meaningful aspects of relationship functioning.